The Influence Of Local Wisdom Characteristics Of The Community Inhabit Megalitics Sites At Napu Valley On The Integrated Social Studies Learning At Junior High Schools In Napu Valley - ., Nuraedah; ., Junarti; Kapile, Charles (KnE Social Sciences, 2023)
In the last few years, the discussion about local wisdom has become an interesting issue. Local wisdom can affect social interaction, especially in education. The existing condition of an area affects the local wisdom adopted by the people living in that area. The purpose of this study is to analyze the relationship between the characteristics of local wisdom on integrated social studies learning. The research location is in Napu Valley, Poso Regency. The area has unique characteristics both the social conditions of the people and the existing conditions of the region. Napu Valley is a valley between hills in the central part of Central Sulawesi Province. The techniques of data collection are literature studies, observation, interviews, and questionnaires. The research method used descriptive methods that describe the relationship between local wisdom factors with integrated social studies learning through related data collection. The research method uses descriptive methods that describe the relationship between local wisdom factors with integrated social. The results indicated that the characteristics of local wisdom have a close and moderate relationship between social studies learning with a value of correlation cooeficient (r2) of 0.62 in Lore Utara Sub-district. 0.76 in Lore Peore Sub-district, and 0.53 in Lore Utara Sub-district. Keywords: Local wisdom; social interaction; integrated social; social studies learning